Queer Kinship on the Edge? Families of Choice in Poland - Mizielińska, Joanna (Transforming LGBTQ Lives, 2022)
Queer Kinship on the Edge explores ways in which queer families from Central and Easter Europe complicate the mainstream picture of queer kinship and families researched in the Anglo-American contexts. The book presents findings from under-represented localities as a starting point to query some of the expectations about queer kinship and to provide insights on the scale and nature of queer kinship in diverse geo-political locations and the complexities of lived experiences of queer families. Drawing on on rich qualitative multi-method study to address the gap in queer kinship studies which tend to exclude Polish or wider Central and Eastern perspectives, it offers a multi-dimensional picture of 'families of choice' improving sensitivity towards differences in queer kinship studies. Through case studies and interviews with diverse members of queer families (i.e. queer parents, their children) and their families of origin (parents and siblings) the book looks at queer domesticity, practices of care, defining and displaying families, queer parenthood familial homophobia, and interpersonal relationships through the life-course. This study is suitable for those interested in LGBT Studies, Sexuality Studies, Kinship and Eastern European Studies.